Optimal composition of a starch-hemp agro-composite materials - Gacoin, A.; Li, A. (Construction and Building Materials, 2023)
The use of Hemp/Lime concrete has gained popularity due to its lightweight, low thermal conductivity, and good sound absorption properties. However, the emission of CO2 from lime and the non-durability and non-recyclability of lime-hemp concrete make it less sustainable. In this paper, we studied new Starch/Hemp agro-composite materials as an alternative building material. The physical and mechanical properties of these materials strongly depend on the mixture of hemp shive and binder, making it challenging to determine the optimal composition for specific applications. This paper presents the experimental results obtained from one hundred and eighty specimens for the optimal composition. We used thirty different mixtures, including three Hemp/Starch (H/S) ratios of 6, 8, and 10, and five mixtures with hemp shive sizes of 5 mm (Hk), 15 mm (Hi), and 20 mm (Hj). We studied and analyzed the influence of the H/S ratio and hemp shive size (Hk, Hi, Hj) on mechanical properties, including density, flexural tensile strength, compressive strength, Young's modulus, and Poisson's ratio. The experimental results demonstrate that the starch-based binder allows for the transfer of mechanical strength to the hemp shive and gives the desired shape to the agro-composite material. The equations describing the evolution of the physical and mechanical characteristics (ρ, σc, σt, E, ν) should help researchers and building professionals manufacture this agro-resource and determine the optimal composition for building based on intended applications.
Keywords: Composition; Hemp shives composite; Mechanical properties; Starch; Stress analysis